Electrochemical Water Oxidation and Stereoselective Oxygen Atom Transfer Mediated by a Copper Complex. Issue 20 (6th February 2018) - Kafentzi, Maria‐Chrysanthi; Papadakis, Raffaello; Gennarini, Federica; Kochem, Amélie; Iranzo, Olga; Le Mest, Yves; Le Poul, Nicolas; Tron, Thierry; Faure, Bruno; Simaan, A. Jalila; Réglier, Marius
Abstract: Water oxidation by copper‐based complexes to form dioxygen has attracted attention in recent years, with the aim of developing efficient and cheap catalysts for chemical energy storage. In addition, high‐valent metal–oxo species produced by the oxidation of metal complexes in the presence of water can be used to achieve substrate oxygenation with the use of H2 O as an oxygen source. To date, this strategy has not been reported for copper complexes. Herein, a copper(II) complex, [(RPY2)Cu(OTf)2 ] (RPY2=N‐substituted bis[2‐pyridyl(ethylamine)] ligands; R=indane; OTf=triflate), is used. This complex, which contains an oxidizable substrate moiety (indane), is used as a tool to monitor an intramolecular oxygen atom transfer reaction. Electrochemical properties were investigated and, upon electrolysis at 1.30 V versus a normal hydrogen electrode (NHE), both dioxygen production and oxygenation of the indane moiety were observed. The ligand was oxidized in a highly diastereoselective manner, which indicated that the observed reactivity was mediated by metal‐centered reactive species. The pH dependence of the reactivity was monitored and correlated with speciation deduced from different techniques, ranging from potentiometric titrations to spectroscopic studies and DFT calculations. Water oxidation for dioxygen production occurs at neutral pH and is probably mediated by the oxidation of a mononuclear copper(II) precursor. It is achieved with a rather low overpotential (280 mV at pH 7), although with limited efficiency. On the other hand, oxygenation is maximum at pH 8–8.5 and is probably mediated by the electrochemical oxidation of an antiferromagnetically coupled dinuclear bis(μ‐hydroxo) copper(II) precursor. This constitutes the first example of copper‐centered oxidative water activation for a selective oxygenation reaction. Abstract : Testing water : High‐valent metal–oxo species produced by the oxidation of metal complexes in the presence of water can be used to achieve substrate oxygenation with the use of water as an oxygen source. Intramolecular and stereoselective oxygen atom transfer is achieved on an N‐substituted bis[2‐pyridyl(ethylamine) indane ligand upon oxidation of copper(II) precursor in water (see figure).